PENGHITUNGAN HARGA POKOK PRODUKSI CV KARYASOKA - Bambang Setyobudi Irianto (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
Based on the results of community service regarding the procedure for calculating the cost of production, it can be concluded as follows: The stages of activities in calculating the cost of production include: receiving orders, making product design proposals, making product design development schedules, making draft designs and sample specifications, calculating cost of goods manufactured, and launching products to the market. The functions involved in the procedure for calculating the cost of production include: marketing function, research and development function, head of production, finance, factory manager and general manager. Documents used in the procedure for calculating the cost of production include: sales orders, new design proposal forms, and sample work sheets. Books (Journals), Notes, Lists, and Reports used in the procedure for calculating the cost of production include: journals on the use of raw materials, proof of cash outflows, product cost cards, cost cards, and finished product reports. The company's internal control elements have been running well because of proper separation of functions, authorization is carried out by the competent authorities, and quality employees.